PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN DIGITAL BERBASIS WEB MENGGUNAKAN METODE WATERFALL - Aziz, Avdela Elia; Erwadi, Yetman (Jurnal Informatika, 2026)
Abstract —  There are still a number of issues with the manual library administration system, including ineffective data recording, challenges with book data searching, and laborious report creation procedures. These problems reduce the quality of library services and hinder the efficiency of library staff, making it urgent to develop a digital solution. The goal of this project is to create a web-based digital library information system that can increase the effectiveness of managing library data. The Waterfall technique, which focuses on two stages—requirements analysis and system design—was employed in this study. Requirements analysis was conducted to identify functional requirements (book data management, member management, borrowing and return transactions, and report generation) and non-functional requirements (data security, usability, and multi-device accessibility). The system involves two main actors: Admin and Member. During the system design stage, Use Case Diagrams, Entity Relationship Diagrams (ERD) with five entities (Book, Category, Member, Borrowing, and Return), and user interface designs were created. The study's findings show that the suggested system design can address issues with the manual method and help library administration procedures become more efficient, organized, and user-friendly.                                                                                                                                         Key word — Information System, Digital Library, Web-Based, System Design, Waterfall